2013
DOI: 10.1155/2013/648061
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Oxidative Stress Injury after Ischemic Stroke in Conscious Rats: Limited Benefits with Apocynin Highlight the Need to Incorporate Long Term Recovery

Abstract: NADPH oxidase is a major source of superoxide anion following stroke and reperfusion. This study evaluated the effects of apocynin, a known antioxidant and inhibitor of Nox2 NADPH, on neuronal injury and cell-specific responses to stroke induced in the conscious rat. Apocynin treatment (50 mg/kg i.p.) commencing 1 hour prior to stroke and 24 and 48 hours after stroke significantly reduced infarct volume in the cortex by ~ 60%, but had no effect on striatal damage or neurological deficits. In situ detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…We too have recently shown that treatment with a high dose of apocynin reduces cortical damage after endothelin-1-induced stroke and reperfusion in rats with a 3 day recovery, but we showed no effect of apocynin treatment on striatal infarcts, as previously reported [217]. This lack of effect was correlated with increased neuronal ROS generation within the penumbra of apocynin-treated rats and we proposed that treatment with apocynin merely delayed the progression of injury over time [217].…”
Section: Inhibitors Of Nadph Oxidasesupporting
confidence: 84%
See 1 more Smart Citation
“…We too have recently shown that treatment with a high dose of apocynin reduces cortical damage after endothelin-1-induced stroke and reperfusion in rats with a 3 day recovery, but we showed no effect of apocynin treatment on striatal infarcts, as previously reported [217]. This lack of effect was correlated with increased neuronal ROS generation within the penumbra of apocynin-treated rats and we proposed that treatment with apocynin merely delayed the progression of injury over time [217].…”
Section: Inhibitors Of Nadph Oxidasesupporting
confidence: 84%
“…We too have recently shown that treatment with a high dose of apocynin reduces cortical damage after endothelin-1-induced stroke and reperfusion in rats with a 3 day recovery, but we showed no effect of apocynin treatment on striatal infarcts, as previously reported [217]. This lack of effect was correlated with increased neuronal ROS generation within the penumbra of apocynin-treated rats and we proposed that treatment with apocynin merely delayed the progression of injury over time [217]. Indeed previous reports showing protective actions of apocynin within the striatum measured infarcts only up to 24 h post-reperfusion, at times when the infarct may not have fully matured in the models used for assessment [154,160,167,176,177].…”
Section: Inhibitors Of Nadph Oxidasesupporting
confidence: 84%
“…In this study we created two doses of apocynin since in literature both the low (20 mg/kg) and high doses (50-100 mg/kg) were used against oxidative stress in different tissues and plasma [9,10,34]. Furthermore in the study of Li et al, apocynin, administered at a dose of 16 mg/kg for 4 weeks, protected against diabetes-induced testicular damage [35].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, a large numbers of studies used the 4-hydroxy-3methoxy-acetophenone (apocynin), a natural, powerful antioxidant compound used in traditional Ayurvedic medicine (1). Although its molecular mechanism is not fully understood, apocynin would impair NOX2 assembly and activation (242), thus resulting as a NOX2-targeted therapeutic strategy against stroke (227). Experimental models of either focal or global cerebral ischemia have supported the neuroprotective role of apocynin.…”
Section: Rationale For Downregulating Ros In Strokementioning
confidence: 99%